Evaluation of helical tomotherapy as an alternative for left-sided breast cancer patients not compliant with deep inspiration breath hold - Kuru, Okan; Goksel, Evren Ozan; Demircan, Niyazi Volkan; Sengoz, Meric (Elsevier, 2024)
Purpose: The aim of this study is to investigate, from a dosimetric perspective, whether helical Tomotherapy (HT) during free breathing (FB) can serve as an alternative technique for treating left-sided breast cancer patients who are unable to comply with the deep inspiration breath hold (DIBH) technique. Material and Methods: For this purpose, the CT images of 20 left breast-only cancer patients acquired in both FB and DIBH phases were utilized. The left breast was contoured as the target volume, while the heart, LAD, ipsilateral and contralateral lungs, and contralateral breast were contoured as organs at risk on the CT images obtained in both DIBH and FB. Planning with the volumetric modulated arc therapy (VMAT) technique was performed on the CT scans obtained in the DIBH (VMAT-DIBH), while planning with the HT technique was carried out on the CT scans obtained in the FB (HT-FB). Subsequently, dosimetric comparison of the plans were done in terms of target coverage and preservation of normal tissues. Results: Both techniques achieved the desired target coverage; however, in terms of D2, Vpres values, Conformity Number (CN), and Homogeneity Index (HI), the HT-FB technique was found to be superior. While the mean doses to the heart were similar for both techniques, doses to the LAD and left lung were found to be superior in plans generated with the HT-FB technique. When compared in terms of contralateral breast and right lung protection, VMAT-DIBH technique was found to be significantly superior. Conclusion: The treatment of left breast-only patients with the HT-FB technique has been observed to provide similar heart protection and better LAD and ipsilateral lung protection compared to the VMAT-DIBH technique without compromising target coverage. However, when the HT-FB technique is used, doses to the contralateral lung and contralateral breast should be carefully evaluated.
Keywords: Left-Sided Breast-only Radiotherapy; VMAT; Helical Tomotherapy; Deep Inspiration Breath-Hold; Free Breathing